Civil Legislators In The Castelo Branco Government: Fundamental Rights And The 1967 Constitution (Revista Direito em Debate, 2022)
the 1967 Constitution, in its art. 150, provided for Fundamental Rights common to Rule of Law. As the Military Dictatorship was marked, before and after 1967, by the impeachment of political rights, censorship and state violence, we seek to investigate the contradiction of the insertion of Fundamental Rights in that constitution. We intend to demonstrate that art. 150 served as a liberal-bourgeois veneer, reflecting the legal culture of legislators in line with the military rhetoric that sought to legitimize their governments as a special form of “democracy”, since they would represent the desires of Brazilian society for the imposition of order and development on the part of of the Armed Forces.